The Impact of Role-playing Games on Developing Empathy of Future Preschool Inclusive Teachers - Komisaryk, Mariya; Kuznietsova, Kateryna; Taniavska, Yaryna; Chuyko, Halyna; Kushniryk, Roksoliana (International Journal of Education and Information Technologies, 2024)
— Inclusive education should be based on the effective involvement of people with disabilities in the educational process to obtain positive results. The work aims to determine the impact of role-playing games on developing empathy of future inclusive teachers. The aim was achieved using the Likert scale, observation, value function calculations, the rank coefficient of the level of effectiveness, and the Cramér criterion. The results of the study showed that it is necessary to ensure that students’ experiences during communication are considered first and foremost for the effectiveness of learning in an inclusive class and the development of empathy (0.93). Therefore, this criterion was primarily considered during the development of learning mechanisms. Training mechanisms for future teachers were intended to ensure the formation of an adaptive function, a communicative function, an understanding of a new approach, and the formation of an educational function. The game-based approach became the foundation of the educational process. A high level of empathy was achieved among 89% of students, which is associated with the development of tolerance. A high level of empathy was reflected in the development of communication (28%), creative activity (27%), and a greater level of restraint (23%). An individual approach in the process of teaching preschoolers influences their achievement of a high level of knowledge. The importance of the work is determining approaches to the development of a high level of empathy among future inclusive teachers using role-playing games, which is important for children’s development. Research prospects are related to the possibilities of developing empathy for future teachers by using the role-playing approach in education and digital technologies
Keywords: —situational tasks, projection of actions, inclusive group, physiological limitations, communicative function, imitation of students' actions, emotionality, psychological state, behavioral reactions.